Spontaneous apoptosis in human thymocytes. - Tiso, M. (1995)
Apoptosis seems to be involved in different stages of immune cell development. In particular, experimental evidence suggests that it is a major form of cell death in the thymus. The present analysis of human thymocytes reveals that a fraction of these cells, cultured in vitro, undergoes spontaneous apoptosis. This observation is based both on molecular (DNA fragmentation) and morphological (electron microscopic) investigations of the cells. The apoptotic thymocytes are CD3- or CD3lo, CD4lo, and CD8lo and do not express Bcl-2 protein. Furthermore, thymocytes die by apoptosis when exposed to pharmacological stimuli, such as tumor necrosis factor-alpha, dexamethasone, ATP, or Ca++ ionophore. Thus the apoptotic machinery in thymocytes can be triggered by an imbalance in growth factors in the in vitro culture media and can be modulated by various biochemical signals. The process of spontaneous apoptosis is independent of mRNA or protein synthesis, as actinomycin D and cycloheximide fail to inhibit this phenomenon. Furthermore, apoptosis seems to require active oxidative phosphorylation, as it is prevented by incubation of the cells with inhibitors of the respiratory chain.